63. A study of cortical and spinal excitability in patients affected by multiple sclerosis and spasticity after oromucosal cannabinoid spray (THC/CBD). Issue 4 (April 2016) - Donato, F.; Turri, M.; Zanette, G.; Tugnoli, V.; Deotto, L.; Teatini, F.; Romito, S.; Moretto, G.; Squintani, G.
Abstract : The therapeutic efficacy of oromucosal cannabinoid spray (THC/CBD) for the treatment of spasticity is well documented by clinical trials, and THC/CBD has been approved in Italy for the treatment of spasticity in multiple sclerosis (MS). Our study aims to assess the neurophysiological correlates of the THC/CBD effect on spasticity in MS. We enrolled 16 MS patients who underwent a neurological examination (together with modified Ashworth scale) and neurophysiological testing. For the assessment of the cortical and spinal excitability, we performed duble-pulse TMS to evaluate LICI, SICI and ICF; we also studied CSP, H/M ratio and H reflex recovery cycle. Clinical and neurophysiological results were tested before and after one month of THC/CBD spray treatment and compared with data obtained from 10 healthy controls. Patients referred a subjective decrease of spasticity after THC/CBD, confirmed by modified Ashworth scale, and showed a significant difference of the H recovery cycle (at ISI 500 ms) and LICI compared to controls, that normalized after THC/CBD. CSP did not differ from healthy subjects. Our data showed that THC/CBD oromucosal spray is effective in spasticity treatment and that it probably acts at spinal and subcortical level by modulating the GABA-ergic inhibitory circuitry.